Diseminasi Teknik Budidaya Tanaman Sayuran secara Terapung di Desa Tanjung Pering: Disseminating the Cultivation of Floating Vegetables in Tanjung Pering Village - Susilawati, Susilawati; Lakitan, Benyamin; Sodikin, Erizal; Harun, M. Umar; Irmawati, Irmawati; Yakup, Yakup; Gustiar, Fitra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The majority of Tanjung Pering Village’s citizens are engaged in vegetable farming. Vegetables are typically grown in gardens on dry land or in marshes on wet soil under dry conditions. Lebak swamps that are flooded for more than six months are generally not used for cultivation, as a result, parts of the village area are not useful for settlement or agriculture. The solution that can be taken is to utilize wetlands with floating cultivation, especially for vegetable crops. After Community Service Activities through mentoring and plot demonstrations, the knowledge and skills of the people of Tanjung Pering Village, North Indralaya District regarding the cultivation of floating vegetable plants can be increased. In conclusion of the activity, the community is interested in trying to cultivate floating plants.